Effect of different track start positions on horizontal take-off velocity of whole-sody center of mass in swimming: A simualtion study - Tanaka, T.; Honjo, T.; Fujimoto, M.; Nagano, A.; lsaka, T. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The objective of this study was to investigate the effects of different track start positions on horizontal take-off velocity of the whole-body center of mass (COM) in swimming. The whole body was modeled as linked rigid-body segments to simulate the track start performance, and a simulation was performce with two different track start positions, with the COM positioned at the rear and low level (RL), and at the front and high level (FH). The results demonstrated that the horizontal take-off velocity was faster for the RL than the FH. The hip joint moments were larger for the RL than the FH on both front and rear legs. Therefore, the COM positioned at the rear and lower level for the track start would contribute to a greater hip joint moment generation, producing a greater horizontal velocity of the COM at take-off.